Silver nanoparticles improved explant disinfection, in vitro growth, runner formation and limited ethylene accumulation during micropropagation of strawberry (Fragaria × ananassa) - Hoàng, Thanh Tùng (2022)
One of the common problems in strawberry (Fragaria × ananassa) micropropagation is the vitrification phenomenon (succulent plantlets, brittle stems, yellow leaves, etc.) leading to the reduction of plantlets quality and low survival rate in the greenhouse. In this study, the effects of silver nanoparticles (AgNPs) on explant disinfection, in vitro growth (shoot multiplication, and root formation), runner formation as well as ethylene accumulation during micropropagation of strawberry were investigated. The results showed that leaf explants treated with 200 mg/L AgNPs solution for 20 min was more effective in explant disinfection and shoot regeneration than using 1 g/L HgCl2. In addition, AgNPs stimulated the growth of shoot and plantlet and as well shortened the duration of root formation (4 days) as compared to those in control without AgNPs during micropropagation. Besides, AgNPs reduced the ethylene gas accumulation in the culture’s vessels of shoots (0.66 ppm) and plants (0.06 ppm) compared to controls (1.77 ppm; 0.15 ppm; respectively). Moreover, AgNPs combination with culture period (5; 10 or 15 days) effect root formation stage and acclimatization in the greenhouse. The plantlets that cultured on MS medium supplemethed with 0.5 mg/L AgNPs during 10 days showed higher survival rate (93.33%) after 15 days as well as runner formation per plant (8.00 runners) after 60 days in greenhouse than those in control.